Tổng hợp một số dẫn xuất của cycloart-23Z-ene-3beta-25-diol và hoạt tính sinh học của chúng - Tuyến, Nguyễn Văn; Hùng, Nguyễn Văn; Chiến, Nguyễn Quyết (Vietnam Journal of Chemistry, 2014)
Cycloart-23Z-ene-3β-25-diol was isolated from the leaves of Aglaia gigantea by bioassay-guided fractionation. This compound showed very good cytotoxicity against human hepatoma (Hep-G2) and KB cells. In oder to investigate the relationship between biological activity and structure of the derivatives of cycloart-23Z-ene-3β-25-diol, we carried out synthesis of several new derivatives and examined their biological activities.